CREATIVE WORK AS A FACTOR OF EFFICIENCY GROWTH - Murat, Ikramov; Nigora, Abdurashidova (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2025)
The article examines the current problem of developing creative work in modern conditions. The author emphasizes the need to find new methods for achieving this, conducts a comparative analysis of the characteristics of mental and physical labor, proposes the